Israf’s Prohibition in QS. al-A’raf : 31 (Abdullah Saeed’s Contextual Approach) - M. Syarif Adi Pramana; Muhammad Saiful Khair (Jurnal test, 2024)
This article discusses Israf’s behavior that occurs today. One form of Israf is a hedonistic lifestyle that aims at personal satisfaction to enjoy worldly life excessively. To satisfy their desires, they always keep up with the times, spending money and time on fun, which can lead to debt and even depression. Allah reminds humans that the primary purpose of life is to prepare for the future by serving and believing in Him, doing good deeds, and living an ethical and moral life. If not responded to wisely, the developments that occur in this modern era will only plunge people into negative things that can endanger themselves and others. This article uses a qualitative method in the form of library research, which took data from several book sources, tafsir books, and Arabic dictionaries to analyze the meaning of Israf in QS. al-A’raf verse 31 using Abdullah Saeed’s contextual interpretation approach. The result is that Israf behavior can be seen based on context. It is not only limited to lifestyle activities that use excessive wealth but also religious fanaticism, high ambition to achieve power, and wasting time on unproductive things, so it is insensitive to conditions in the surrounding community environment.